The impact of decentralization policies: the environmental performance applied to municipalities of the Amazon - da Silva, Benedito Evandro Barros; Azevedo-Ramos, Claudia; Farias, Hilder André Bezerra (Desenvolvimento e Meio Ambiente, 2019)
The historical environmental problems in the Amazon urge greater governance and transparency at the municipal level. The decentralizing of municipal environmental management (MEM) is an ongoing process in the Brazilian Amazonbut a monitoring mechanism is missing. We used an index (iMEM) derived by factorial analysis to rank the environmental management performance of 143 municipalities in Pará state at the beginning of the decentralizing process (2009) and six years after that (2015). Multiple regression analysis indicated that iMEM was positively affected by factors such as population, communication and protected areas in the municipalities and negatively affected by rural credit, GDP and property registration program. Decentralizing measures seem to be more politically than environmentally effective since only 21.7% of 143 municipalities were classified as having good environmental management in 2015. Pará’s poorly performing municipalities in both periods illustrate regions where unsustainable and misguided national policies were fostered in the 70s. The monitoring of the decentralization progress and synergic policies is crucial for the effectiveness of the policy in the Amazon.